Correlation between dental conditions and comorbidities in an elderly Japanese population: A cross-sectional study. Issue 24 (June 2018) - Ide, Kazuki; Seto, Kahori; Usui, Tomoko; Tanaka, Sachiko; Kawakami, Koji
Abstract : Abstract: The purpose of this study was to investigate the correlation between dental conditions and comorbidities in an elderly population in Japan. A database constructed using data obtained from 12 nursing homes in Japan was used in this study. The study period ranged from January 2014 to December 2015, and elderly individuals with dental and other medical records were included in the analysis. Linear regression models were used to analyze univariate and multivariate correlation between dental conditions, comorbidities, and other sociodemographic/clinical backgrounds. After excluding individuals with missing data, 289 elderly individuals (107 men and 182 women; mean age, 85 years) were included in the analysis. These individuals had an average of 11.6 teeth, and the number decreased with older age ( P  < .001). The average number of decayed teeth was 1.4. A total of 116 subjects (40.1%) had dementia. In terms of comorbidities, dementia was not significantly associated with the number of present teeth ( P  = .56), but it was associated with the number of decayed teeth ( P  = .018). This association was also observed after adjusting for confounding variables in the multivariate regression analysis ( P  = .030). The number of decayed teeth was associated with dementia. While causality cannot be inferred from these observational results, the findings indicate that dental health could represent a marker of impending dementia, and probably represent a marker of general health status in the elderly population. Additional longitudinal studies are highly desirable to understand the causal relationships between dental conditions and comorbidities. Abstract : Supplemental Digital Content is available in the text